2020
DOI: 10.1371/journal.pone.0240722
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive treatment of microvascular angina in overweight women – a randomized controlled pilot trial

Abstract: Aims Coronary microvascular dysfunction (CMD) carries a poor cardiovascular prognosis and may explain angina in women without obstructive coronary artery disease (CAD). Currently, no evidence-based treatment for CMD exists. We investigated whether reducing cardiovascular risk factors improves symptoms and microvascular function in women with non-endothelial dependent CMD and no obstructive CAD. Methods We randomized 62 women aged 40–75, with body mass index (BMI) >25 kg/m2, angina ≥monthly, and coronary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Similarly, it appears that weight loss and improved exercise capacity ameliorate CMD, reflected in increases in CFR assessed by Doppler echocardiography of the left anterior descendent artery [ 94 , 95 ]. Conversely, another trial showed that major weight loss resulted in significantly improved angina symptoms among women with microvascular angina but without amelioration of coronary microvascular function [ 96 ]. Further studies are needed to systematically determine the impact of weight loss on CMD.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Similarly, it appears that weight loss and improved exercise capacity ameliorate CMD, reflected in increases in CFR assessed by Doppler echocardiography of the left anterior descendent artery [ 94 , 95 ]. Conversely, another trial showed that major weight loss resulted in significantly improved angina symptoms among women with microvascular angina but without amelioration of coronary microvascular function [ 96 ]. Further studies are needed to systematically determine the impact of weight loss on CMD.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…To date, a number of small randomized clinical trials or nonrandomized observational studies have reported cardiovascular outcomes in patients with CMVD 140,141 . Large‐sample randomized clinical trials with cardiovascular events as endpoints are underway.…”
Section: Treatment Of Cmvdmentioning
confidence: 99%
“…Lifestyle management in patients with CMVD is similar to that in those with atherosclerosis and includes healthy diet, smoking cessation, and weight control 141,159 . Individualized exercise programs and cardiac rehabilitation can improve angina symptoms, exercise tolerance, quality of life, and CFR in patients with CMVD 160–162 .…”
Section: Treatment Of Cmvdmentioning
confidence: 99%
“…These anti-ischaemic agents achieve their therapeutic effects via different targets (table 2) and hence are often used in combination. In addition to these conventional agents, novel anti-ischaemic agents have been shown to reduce ischaemia or angina in patients with INOCA including phosphodiesterase-357 and phosphodiesterase-576 inhibitors, rho kinase inhibitors,9697 angiotensin converting enzyme inhibitors72 and estradiol,54 as well as lifestyle risk factor modification8791 (tables 3 and 4).…”
Section: What Are the Treatment Targets?mentioning
confidence: 99%